Nasal CPAP reduces systemic blood pressure in patients with obstructive sleep apnoea and mild sleepiness. Issue 12 (23rd August 2006) - Hui, D S; To, K W; Ko, F W; Fok, J P; Chan, M C; Ngai, J C; Tung, A H; Ho, C W; Tong, M W; Szeto, C-C; Yu, C-M
Abstract : Background: A randomised controlled study was undertaken to examine the effect of nasal continuous positive airway pressure (CPAP) on 24 hour systemic blood pressure (BP) in patients with obstructive sleep apnoea (OSA). Methods: Patients were fitted with an ambulatory BP measuring device as outpatients during normal activities and recorded for 24 hours before starting therapeutic or subtherapeutic (4 cm H2 O) CPAP treatment. BP monitoring was repeated before completion of 12 weeks of treatment. The primary end point was the change in 24 hour mean BP. Results: Twenty three of 28 participants in each treatment arm completed the study. There was no significant difference between the two groups in age, body mass index, Epworth Sleepiness Score, apnoea-hypopnoea index, arousal index, and minimum Sao 2 . Twenty four patients were hypertensive. The pressure in the therapeutic CPAP group was 10.7 (0.4) cm H2 O. CPAP usage was 5.1 (0.4) and 2.6 (0.4) hours/night for the therapeutic and subtherapeutic CPAP groups, respectively (p<0.001). After 12 weeks of treatment there were significant differences between the two CPAP groups in mean (SE) changes in 24 hour diastolic BP (−2.4 (1.2) v 1.1 (1.0) mm Hg (95% CI −6.6 to −0.5), p = 0.025); 24 hour mean BP (−2.5 (1.3) v 1.3 (1.1) mm Hg (95% CI −7.2 to −0.2), p = 0.037); sleep time systolic BP (−4.1 (2.1) v 2.2 (1.8) mm Hg (95% CI −11.8 to −0.7), p = 0.028); and sleep time mean BP (−3.6 (1.7) v 1.3 (1.4) mm Hg (95% CI −9.2 to −0.4), p = 0.033). Conclusions: Compared with subtherapeutic CPAP, 12 weeks of treatment with therapeutic CPAP leads to reductions in 24 hour mean and diastolic BP by 3.8 mm Hg and 3.5 mm Hg, respectively, in mildly sleepy patients with OSA.